A theranostic agent for cancer therapy and imaging in the second near-infrared window - Ma, Zhuoran (Nano Res, 2018)
Theranostic nanoparticles are integrated systems useful for simultaneous diagnosis and imaging guided delivery of therapeutic drugs, with wide ranging potential applications in the clinic. Here we developed a theranostic nanoparticle (~ 24 nm size by dynamic light scattering) p-FE-PTX-FA based on polymeric micelle encapsulating an organic dye (FE) fluorescing in the 1,000–1,700 nm second near-infrared (NIR-II) window and an anti-cancer drug paclitaxel. Folic acid (FA) was conjugated to the nanoparticles to afford specific binding to molecular folate receptors on murine breast cancer 4T1 tumor cells. In vivo, the nanoparticles accumulated in 4T1 tumor through both passive and active targeting effect. Under an 808 nm laser excitation, fluorescence detection above 1,300 nm afforded a large Stokes shift, allowing targeted molecular imaging tumor with high signal to background ratios, reaching a high tumor to normal tissue signal ratio (T/NT) of (20.0 ± 2.3). Further, 4T1 tumors on mice were completed eradicated by paclitaxel released from p-FE-PTA-FA within 20 days of the first injection. Pharmacokinetics and histology studies indicated p-FE-PTX-FA had no obvious toxic side effects to major organs. This represented the first NIR-II theranostic agent developed.